Phase transition of polybutene-1 ionomers: Influences of ion content and branch length. (16th June 2021) - Li, Tao; Liu, Long; Lou, Yahui; Li, Wei; Ma, Guiqiu; Ma, Zhe
Abstract: The phase transition behaviors from the tetragonal form II to the trigonal form I of polybutene-1 ionomers with various ion contents and branch lengths were studied by means of differential scanning calorimetry. In the ionomers studied, ionic functional groups were located at the end of the branches incorporated, so ion content was varied with the incorporation ratio and, branch length was tuned by the distinct co-monomers of 6-iodo-1-hexene and 18-iodo-1-octadecene. The results show that although the branches introduced retard the II-I phase transition in reference copolymers, after introduction of ions, the ionomers exhibit the largely accelerated kinetics of the solid II-I phase transition. Interestingly, it was found that the phase transition exhibits a non-monotonic dependence on the ion content and for the ionomers with 4-carbon branches, the optimal ion content to obtain the maximum transition degree is around 2.6 mol%. This is probably due to the cooperative effects of the formation of intercrystalline links by the ion aggregates in ionomers, 1) the enhanced transfer of internal stress for nucleation and 2) the restricted chain mobility for adjusting segmental packing. Furthermore, the II-I phase transition can be further accelerated by increasing the 4-carbon branch to the 16-carbon branch via copolymerizing 18-iodo-1-octadecene as the comonomers. These results provide the helpful guide to the molecular design of polybutene-1 ionomer materials. Graphical abstract: Image 1 Highlights: The introduction of ionic groups can effectively accelerate the solid II-I phase transition in polybutene-1 ionomers. The kinetics of II-I phase transition in ionomers exhibits the non-monotonic dependence on the ion content. The II-I transition kinetics could be accelerated by increase the length of branches that connect ionic functional groups and backbone.